Analysis of Regional Economic Competitiveness of Gorontalo Province (Case Study of Gorontalo Province Corn Commodity) - Ivan Rahmat Santoso; Fahrudin Zain Olilingo (Gorontalo State University, 2019)
This study aims to determine the analysis of regional economic competitiveness in Gorontalo Province by looking at the value of export of superior corn commodity agriculture. This research covers regional areas in Gorontalo Province. The specific objective to be achieved is to obtain analytical data on the economic competitiveness of the Gorontalo Province in terms of the competitiveness of corn commodity exports. This list is expected to be an input for stakeholders to issue policies in increasing economic competitiveness in corn commodities in Gorontalo Province. This research was carried out in Gorontalo Province with objects in 5 districts and 1 city in Gorontalo Province detecting the competitiveness of each region. The method of analysis of this study uses the RCA (Revealed Comparative) comparative analysis method with the time of the 2013-2017 study. The results of the RCA (Revealed Comparative Advantage) analysis describe the competitiveness of Gorontalo Province's corn commodity exports experiencing fluctuations in which Gorontalo Province's corn commodity exports in 2014, 2015 and 2017 had strong competitiveness, while in 2013 and 2016 Gorontalo Province's maize commodity decreased due to that year Gorontalo Province did not export corn besides the absence of exports because domestic corn prices were quite good.